THE EFFECT OF TRUST, SECURITY, AND TECHNOLOGY READINESS ON THE ADOPTION OF CLOUD ACCOUNTING - Aisyah Hamida Fitrios; Ruhul Fitrios; Restu Agusti; Supriono (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study aims to examine the influence of trust, security, and technology readiness on the adoption of cloud accounting (ACA) among Micro, Small, and Medium Enterprises (MSMEs) in Pekanbaru City. A quantitative approach was employed using survey data collected from food-sector MSMEs. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through SmartPLS 4. The findings indicate that trust, security, and technology readiness significantly influence ACA. Among these factors, security emerged as the strongest predictor, followed by technology readiness and trust. The results support the Technology–Organization–Environment (TOE) Framework, suggesting that technology-related factors play a critical role in ACA among MSMEs. This study contributes to the literature on ACA among Indonesian MSMEs and provides practical implications for policymakers and service providers in promoting digital transformation.